Perlindungan Hukum bagi Korban Penipuan Investasi (Strudi Kasus di Kota Palembang) - adm-jurnal adm-jurnal; mila surahmi (Fakultas Hukum Universitas Sjakhyakirti Palembang, 2019)
Developments in Economic field bring big impact on crime in community. One mode that develops is a fraud with an effort to compile a fund to benefit through investments with the lure of a big yield. But in the attempt, such assessment is nothing but a returns to the investor profits. These developments were not accompanied by an adequate knowledge and understanding of the economic and financial on business of community. So many are popping up due to business investment mode. Legal protection for victims is essential because in fact, the resolution of criminal cases found less crime victims obtain adequate legal protection. This has to be one of problems in this research, especially in this case, investments found victim protection in Palembang often got barriers. Thus, required the formulation of the victims protection concept which can provide adequate judicial protection not only by providing penalties on crime perpetrators but also victims recovery so as to create a balance and bring a sense of peace within the community and embodied justice. This research is empirical. Data were collected through interviews and a literatre study. Using the sociological approach. From this research results, legal protection of investment fraud victims in Palembang got barriers due to several factors including: (a) legislation: in practice often got barriers in the process of handling crime on this investment fraud; (b) public awareness are reluctant to provide reports and testimony; (c) facilities and infrastructure; (d) law enforcement officers that number is still lacking. From some of the barriers and challenges that exist, it necessary law reform to provide legal protection of victims.